Pelatihan Simulasi Electronics Flight Instrument System Buatan Karya Anak Bangsa untuk Siswa SMK Negeri 12 Bandung - Ema Ema; Nina Hendrarini; Simon Siregar; Muhammad Ihsan Ismail (Politeknik Caltex Riau, 2023)
Presidential Instruction Number 9 of 2016 regarding the Revitalization of Vocational High Schools (SMK) emphasizes the importance of Vocational Education, which is education aimed at mastering practical skills in specific fields. Students are equipped with both theoretical knowledge and practical implementation. In order to develop vocational education in line with the competency needs of graduates (the